Public Sector Collective Bargaining - Finkelman, Jacob (Relations industrielles / Industrial Relations, 1986)
The author traces the origins and development of public sector negotiations in Canada. Heputs the accent on several aspects such as: the determination of bargaining units, the definition of what is negotiable, major problems encountered and ways of resolving them, the determining of essential services. In the light offorty years of experience, the author cornes to the conclusion that granting the right to strike in the public sector was a mistake. He also takes position against the merger ofthe Canadian Labour Relations Board (CLRB) and the Public Service Staff Relations Board (PSSRB).